Th1/Th2 cytokines and ICAM-1 levels post-liver transplant do not predict early rejection - E. Granot; A. Tarcsafalvi; S. Emre; P. Sheiner; S. Guy; M. E. Schwartz; P. Boros; C. M. Miller (Hindawi Limited, 2000)
Th1 derived cytokines IFN-γ and IL-2, Th2 cytokine IL-4, and ICAM-1 have been implicated in liver allograft rejection. In order to determine whether monitoring of cytokine profiles during the first days post-liver transplant can predict early rejection we measured IFN-gg, IL-2, sIL-2 receptor, IL-4 and ICAM-1 in 22 patients, in plasma samples obtained within 4h after liver perfusion (baseline) and between postoperative days (POD) 3-6. ICAM-1 and sIL-2R levels at POD 3-6 were significantly higher than at baseline but did not differ in presence or absence of rejection. Mean percentage increase of ICAM-1 levels was significantly lower in patients with Muromonab-C3 Orthoclone OKT3 (J.C. Health Care) (OKT3) whereas percentage increase of sIL-2R levels was higher in OKT3-treated patients. IFN-γ levels at POD 3-6 increased from baseline while IL-4 levels were unchanged. Levels of IFN-γ, IL-4 and their ratios did not correlate with rejection or immunosuppressive therapy. Thus, Th1/Th2 cytokine monitoring during the first week post-transplant does not predict early rejection and immunosuppressive therapy is the predominant factor affecting ICAM and sIL-2R levels after liver transplantation.